Hubungan kepatuhan konsumsi tablet Fe dengan kejadian anemia pada remaja putri kelas x - Safitri, Kana; Kurniawati, Herlin Fitriana; Fitriahadi, Enny (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Anemia is a common health problem among female adolescents due to iron deficiency, particularly because of increased iron requirements during growth and blood loss during menstruation. One preventive measure is the regular consumption of iron tablets, but compliance rates remain low. Purpose: To determine the relationship between iron tablet consumption compliance and the incidence of anemia among female high school students in grade X at State High School 2 Yogyakarta. Method : The study used a quantitative cross-sectional design with a sample size of 124 respondents selected through purposive sampling. Data were collected through questionnaires and Hb level tests, then analyzed using the Chi-Square test. Results: Showed that 41.9% of respondents were compliant and 58.1% were non-compliant in consuming iron tablets. Most of the non-anemic respondents were compliant (96.2%), while the majority of anemic respondents were non-compliant (68.1%). The Chi-Square test showed a p-value = 0.000 (p < 0.05), indicating a significant relationship between compliance with iron tablet consumption and the incidence of anemia. Conclusion: Non-compliance with iron tablet consumption increases the risk of anemia in adolescent girls, thus requiring improved education and supervision in the implementation of iron supplementation programs. Keywords: Adolescent Girls; Anemia; Compliance; Iron Tablets. Pendahuluan: Anemia merupakan masalah kesehatan yang sering terjadi pada remaja putri akibat kekurangan zat besi, terutama karena peningkatan kebutuhan selama masa pertumbuhan dan kehilangan darah saat menstruasi. Salah satu upaya pencegahan adalah konsumsi tablet tambah darah (Fe) secara rutin, namun tingkat kepatuhan masih rendah. Tujuan: Untuk mengetahui hubungan kepatuhan konsumsi tablet Fe dengan kejadian anemia pada remaja putri kelas X. Metode: Penelitian menggunakan desain kuantitatif cross sectional dengan jumlah sampel 124 responden yang dipilih secara purposive sampling. Data dikumpulkan melalui kuesioner dan pemeriksaan kadar Hb, kemudian dianalisis menggunakan uji Chi-Square Hasil: Sebanyak 41.9% responden patuh dan 58.1% tidak patuh mengonsumsi tablet Fe. Sebagian besar responden tidak anemia adalah yang patuh (96.2%), sedangkan mayoritas responden anemia tidak patuh (68.1%). Uji Chi-Square menunjukkan p-value = 0.000 < 0.05. Simpulan: Ketidakpatuhan konsumsi tablet Fe meningkatkan risiko anemia pada remaja putri, sehingga diperlukan peningkatan edukasi dan pengawasan dalam pelaksanaan program suplementasi Fe. Kata Kunci: Anemia; Kepatuhan; Remaja Putri; Tablet Fe.